Searching for the State in British Legal Thought : Competing Conceptions of the Public Sphere / [electronic resource] - McLean, Janet (Cambridge : Cambridge University Press, 2012)
Janet McLean explores how the common law has personified the state and how those personifications affect and reflect the state's relationship to bureaucracy, sovereignty and civil society, the development of public law norms, the expansion and contraction of the public sphere with nationalization and privatization, state responsibility and human rights. Treating legal thought as a variety of political thought, she discusses writers such as Austin, Maitland, Dicey, Laski, Robson, Hart, Griffith, Mitchell and Hayek in the context of both legal doctrine and broader intellectual movements.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).